My Nation Effectively Utilizes Traditional KPOTI Game Media Through Sustainable Culture - Gandasari, Maharani Fatima; Yantiningsih, Erna (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Objectives. This study seeks to examine the impact of traditional game media kpoti, guided by the slogan "lestari budayaku bugar bangsaku." Materials and Methods. A quantitative descriptive method was employed, utilizing a discussion approach and implementing direct practice. The study was carried out with KPOTI Pontianak, involving approximately 36 participants from 10 regions in West Kalimantan. Data was obtained through observation and survey methods. Results. The findings of the study demonstrate that the traditional games employed exhibit an 80% effectiveness in the cognitive domain, specifically in the game of gobak sodor. The minimal difficulty anticipated in grasping one of the traditional game options, specifically gobak sodor, arises from the fact that this game is relatively easy to play and is regarded as familiar or frequently engaged in. The emotional dimension of this traditional game demonstrates an average percentage of 86%, as observed through the attitudes and behaviors of participants engaged in the activity. The cognitive aspect demonstrates a notable percentage value of 90%, evidenced by the substantial enhancement in the participants' motor learning capabilities. Conclusion. The results of the study indicate that the Gobak Sodor game has a significant contribution in increasing physical activity as well as cognitive, affective, and psychomotor aspects of participants. This game is not only a means of entertainment but also plays a role in preserving cultural heritage and improving physical health. As a recommendation for further researchers, it is advisable to conduct further research on the long-term impact of involvement in traditional games on physical and mental health. In addition, further exploration is needed regarding the application of traditional games in the physical education curriculum so that the benefits can be more optimally felt by the younger generation.